You’ll Never Walk without Metaphor: A Study on the Football Chants - Kaya, Sabri; Argan, Metin; Özgen, Caner; Yetim, Gözde; İlbars, Büşra (Pamukkale Üniversitesi, 2020)
[Abstract Not Available]
Keywords: [Keywords Not Available]